High prevalence of tobacco use and exposure to secondhand tobacco smoke among adolescents in low- and middle-income countries - Wang, Liang; Mamudu, Hadii M.; Collins, Candice; Wang, Youfa (Annals of Translational Medicine, 2017)
Although tobacco use remains the leading cause of preventable deaths worldwide, smoking rates continue to increase in many low- and middle-income countries (LMICs) (1,2). The study by Xi et al. shows that among 173,144 adolescents aged 12–15 years in the Global School-based Health Survey (GSHS) and 155,117 adolescents aged 13–15 years in the Global Youth Tobacco Survey (GYTS), 13.6% were current tobacco users (3), which is consistent with previous studies (4,5). Thus, this study highlights the need to prevent smoking in young people through measures such as ban on sale of tobacco to minors.